Mermaid sister - Fraser, Mary Ann (Walker & Co. : Distributed to the trade by Holtzbrinck Publishers, 2008)
Shelly has always wanted a sister, so when she meets Coral, a mermaid, and brings her home, it seems like her wish has been granted.